2017
DOI: 10.18632/oncotarget.16874
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of the sodium glucose cotransporter 2 inhibitor tofogliflozin on diethylnitrosamine-induced liver tumorigenesis in obese and diabetic mice

Abstract: Sodium glucose cotransporter 2 inhibitors are expected to ameliorate the abnormalities associated with metabolic syndrome including non-alcoholic fatty liver disease. In this study, we investigated the effects of the sodium glucose cotransporter 2 inhibitor tofogliflozin on the development of non-alcoholic fatty liver disease-related liver tumorigenesis in C57BL/KsJ-+Leprdb/+Leprdb obese and diabetic mice. The direct effects of tofogliflozin on human liver cancer cell proliferation were also evaluated. Mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 53 publications
(75 reference statements)
6
47
0
Order By: Relevance
“…However, Obara et al has demonstrated that liver cancer cell growth was not directly suppressed by tofogliflozin, other kind of SGLT2-I, in contradiction to our in vitro results. 16 Their report also showed that tofogliflozin treatment did not potently affect the proliferation of liver cancer cells even under hyperglycemic and insulin resistance-mimicking conditions. These findings are of interest; the effects on liver cancer cell proliferation differ according to the type of SGLT2-I.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, Obara et al has demonstrated that liver cancer cell growth was not directly suppressed by tofogliflozin, other kind of SGLT2-I, in contradiction to our in vitro results. 16 Their report also showed that tofogliflozin treatment did not potently affect the proliferation of liver cancer cells even under hyperglycemic and insulin resistance-mimicking conditions. These findings are of interest; the effects on liver cancer cell proliferation differ according to the type of SGLT2-I.…”
Section: Discussionmentioning
confidence: 97%
“…Diabetes is widely recognized as one of the most crucial risk factors for HCC, and various reports have provided clinical evidence supporting the preventive effects of pharmacological T2DM regulation on hepatocarcinogenesis . In addition to metformin and DPP4‐Is, a recent animal study demonstrated that SGLT2‐I suppresses diethylnitrosamine‐induced hepatocarcinogenesis in diabetic mice . Therefore, SGLT2‐Is would be expected to exert additional effects on HCC in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, tofogliflozin has demonstrated chemopreventive activity on diethylnitrosamine‐induced hepatocellular carcinoma related to obesity in rats whereas canagliflozin has shown to attenuate hepatocellular carcinoma development in a non‐alcoholic hepatic steatosis model in melanocortin 4 receptor‐deficient mice induced via western diet …”
Section: Effect Of Sglt2 Inhibitors On Hepatic Disordersmentioning
confidence: 99%
“…It has been suggested that the favourable pharmacological actions of SGLT-2 inhibitors in the treatment of hepatic steatosis is not only as a result of its insulin-independent anti-hyperglycaemic effect and caloric loss subsequent to glycosuria, but also because of their capability in balancing adipose and non-adipose tissues as well as in regulating energy homeostasis 24 Interestingly, tofogliflozin has demonstrated chemopreventive activity on diethylnitrosamine-induced hepatocellular carcinoma related to obesity in rats whereas canagliflozin has shown to attenuate hepatocellular carcinoma development in a non-alcoholic hepatic steatosis model in melanocortin 4 receptor-deficient mice induced via western diet. 24,25 An open-label, non-randomized clinical study involving 79 patients concluded that luseogliflozin significantly ameliorated alanine transaminase, aspartate transaminase, as well as γ-glutamyl transpeptidase levels in patients suffering from hepatic impairment in conjunction with T2DM. These results indicate towards the potential application of luseogliflozin in the therapy of T2DM patients with liver injury.…”
Section: Effec T Of Sg Lt2 Inhib Itor S On Hepatic D Isorder Smentioning
confidence: 99%